Physiological Adaptations Of The External Respiratory System In Children Living In The Southern Near Aral Sea Region - Nadira Mirametova,; Gulayim Serekeeva,; Gulnaz Begdullaeva,; Gulchehra Kudeshova,; Gaukhar Dosjanova, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The Southern Near Aral Sea region is marked by its arid climate and the continuing ecologic crisis linked with the desiccation of the Aral Sea, which resulted in sharp environmental complications. The study is designed to assess the physiological adaptations of the external respiratory system in children residing in this region, who have to face a continuous exposure to a dry and dust-laden atmosphere. Utilizing a cross-sectional study design, we measured important respiratory parameters, pulmonary function, and nasal filtration efficiency in a representative cohort of 200 children aged 6-16 years. Comprehensive data were collected on spirometry tests, nasal resistance, and mucociliary clearance evaluations. The results revealed remarkable structural and functional nasal passages adaptation, such as hypertrophy of the nasal tissues, changes in the nasal airflow resistance, and improvement in the efficiency of the mucociliary clearance. In addition, pulmonary function tests indicated age-dependent differences in lung capacity and expiratory flow rates, which suggest physiological adaptation to chronic exposure to dust particles in the air. These findings underpin the body's ability to adapt to chronic environmental stressors during critical growth and development periods. The findings presented in this study provide essential information about the health hazards children in ecologically affected areas may face, while emphasizing targeted health interventions that may lessen the long-term effects environmental hazards can have on respiratory health.